Comprehensive Safety and Quality Profiling of Bottled Drinking Water in Tripoli, Libya: A Combined Chemical and Microbiological Assessment - Mansor S. Bofaris (African Journal of Advanced Pure and Applied Sciences, 2026)
Bottled drinking water has become an increasingly important source of potable water worldwide, particularly in regions where concerns regarding the safety of tap water and the reliability of public water supply systems persist. This study aimed to evaluate the physicochemical and microbiological quality of selected bottled drinking water brands and to assess their compliance with Libyan drinking water standards and the World Health Organization (WHO) guidelines. A total of ten commercially available bottled water brands (Bs1–Bs10) were analyzed. Physicochemical parameters including pH, total dissolved solids (TDS), total hardness, bicarbonate (HCO₃⁻), chloride (Cl⁻), sulphate (SO₄²⁻), sodium (Na⁺), calcium (Ca²⁺), magnesium (Mg²⁺), and potassium (K⁺) were determined using standard analytical methods such as pH meter measurement, conductivity-based TDS determination, EDTA titration for hardness, acid–base titration for bicarbonate, argentometric titration for chloride, turbidimetric determination for sulphate, and flame photometry or atomic absorption spectrophotometry for major cations. Microbiological quality was assessed by determining the total viable count (TVC) at 22°C for 72 h and at 37°C for 48 h, as well as the presence of total coliforms and Escherichia coli. The results showed that TVC values ranged from 0 to 2 CFU/ml at 22°C and from 0 to 1 CFU/ml at 37°C. Total coliforms and E. coli were not detected in any of the analyzed samples. Overall, the results indicated that all bottled water brands complied with both Libyan standards and WHO guidelines for drinking water quality. The physicochemical parameters were within acceptable limits, while the absence of indicator bacteria confirmed the microbiological safety of the examined samples. Continuous monitoring of bottled water quality is recommended to ensure consumer protection and maintain public health standards.